Semantic dominants of 2020 neologisms as a means of coding reality in the Russian language - Elena V. Marinova (Russian Language Studies, 2022)
The relevance of the research is explained by the insufficient studying of the phenomenon of repeating semes in neologisms of a certain time period in the aspect of the interpretative function of language. The purpose of the study is to analyze the semes in the semantic structure of the neologisms of the coronavirus era and to characterize the part of linguistic worldview in the crisis period. The research material included occasional words recorded in Russian media and thematically connected with one theme - the 2020 pandemic. The source of the research is “The Dictionary of Russian Language of Coronavirus Epoch.” The research was conducted within the framework of sociolinguistics with the method of componential analysis of semantics, word-building and context analyzes. In the process of the research, the thematic subgroups were identified; in each subgroup, the occasional nominations were revealed; the means of evaluation were determined (some productive bases - for compounds; word-building formants - for affixal derivatives), and a general interpretive seme was determined (based on the contextual meaning). Finally, the total number of the words connected with a semantic dominant was determined. These data are presented in the summary table which demonstrates the percentage of representation, and hence the degree of significance of each dominant in the process of language coding of reality. As a result of the study, the semantic dominants uniting the occasional words of different authors and demonstrating the typical assessments of COVID-19 are revealed; the degree of frequency of semantic dominants is determined. The novelty of the research is explained by the specifics of the conducted semantic analysis: for the first time, common semes reflecting the peculiarities of the emotional and mental state of the society are revealed on a significant homogeneous array of word-building derivatives.